2012
DOI: 10.18388/abp.2012_2088
|View full text |Cite
|
Sign up to set email alerts
|

Stigmasterol blocks cartilage degradation in rabbit model of osteoarthritis.

Abstract: Stigmasterol has been shown exihbit anti-osteoarthritic properties in vitro studies. However, the in vivo effects of stigmasterol on cartilage are still unclear. This study investigated the anti-osteoarthritic properties of stigmasterol on cartilage degradation in a rabbit model of osteoarthritis (OA). Twenty rabbits underwent bilateral anterior cruciate ligament transection (ACLT) to induce OA. Five rabbits were used as normal control. Two weeks after operation, the rabbits were randomly divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 26 publications
2
29
1
Order By: Relevance
“…Therefore, cartilage pooled from the medial side was used for gene expression analyses to elucidate early changes. Consistent with the literature, after ACLT transcriptional downregulation of ACAN and upregulation of MMP1 , MMP3 , MMP13 and ADAMTS5 (Bluteau et al , 2001; Chen et al , 2012; Hotta et al , 2005; Majima et al , 2002; Wu et al , 2008) were observed. Our findings agreed with the work of Hart and colleagues (Majima et al , 2002), who report a dramatic increase in MMP13 mRNA levels 3 weeks post ACLT in all cartilage regions, which then declined rapidly by 8 weeks, suggesting that MMP13 is involved in early remodelling of matrix in response to ACLT.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, cartilage pooled from the medial side was used for gene expression analyses to elucidate early changes. Consistent with the literature, after ACLT transcriptional downregulation of ACAN and upregulation of MMP1 , MMP3 , MMP13 and ADAMTS5 (Bluteau et al , 2001; Chen et al , 2012; Hotta et al , 2005; Majima et al , 2002; Wu et al , 2008) were observed. Our findings agreed with the work of Hart and colleagues (Majima et al , 2002), who report a dramatic increase in MMP13 mRNA levels 3 weeks post ACLT in all cartilage regions, which then declined rapidly by 8 weeks, suggesting that MMP13 is involved in early remodelling of matrix in response to ACLT.…”
Section: Discussionsupporting
confidence: 91%
“…15 In the current study, we demonstrated that Ang II induced the cell proliferation and cell cycle arrest at the S phase, and inhibited cell apoptosis in A7r5 cells, which is in line with other findings on vascular smooth muscle cells. 10,19,20 In this study, we have provided the first evidence that treatment with stigmasterol significantly inhibits the excessive proliferation and cell cycle arrest, induce apoptosis, and counteract the detrimental effects induced by angiotensin II in A7r5 cell lines. ***P < 0.001 represents significant difference when compared with the control group (without treatment with stigmasterol or Ang II).…”
Section: Discussionmentioning
confidence: 83%
“…32 Stigmasterol existing in HL and RAS, was demonstrated to block cartilage degradation in the rabbit model of OA, showing potential anti-osteoarthritic properties. 33,34 Another unique key active ingredients in FK, boswellic acid, was found significant synovial concentration and therapeutic efficacy in the mouse model. 35 It could also improve physical and functional ability and reduce the pain and stiffness according to a pilot, randomized, double-blind, placebo-controlled trial.…”
Section: Discussionmentioning
confidence: 99%